The Drone’s Gaze, Religious Perspective on Privacy and Human Dignity in the Age of Surveillance Mentioning Security Threats & Regulatory Gaps (Al-Qamar, 2024)
Without managing regulatory framework’s evolution simultaneously, the rapid commercialization of drones has supported prevalent accessibility. Due to the scarce of strict policies on the drone sales, registration and operations has resulted in noteworthy privacy breaches and security concerns.  This kind of illegal prevalence of technology challenges to law enforcement, empowering illegitimate surveillance, airspace desecrations, and unofficial data collection. The paper investigates about the deficiency of lawful ethical concerns, and suggests about the essential advancements for true operational drone governance. The study offers recommendations for severer policies and enforcement mechanisms after analysis of comparative religious perspectives, case studies and international regulatory frameworks.
Keywords: Drone; Commercialization; Technology; Surveillance; Religious